Conflict resolution and ontological security : peace anxieties - Rumelili, Bahar (PRIO new security studies, 2015)
"This volume highlights the ways in which the prospect of peace can generate anxieties and consequently set in motion social and political processes that reproduce and reactivate conflicts. In analysing this issue, the volume builds on the notion of ont